Eggshell speckling in a passerine bird reveals chronic long-term decline in soil calcium - Gosler, A; Wilkin, T (Taylor and Francis, 2017)
Capsule: Long-term changes in eggshell speckling correlated temporally and spatially with declining soil calcium in an English Great Tit Parus major population. Aims: Eggshell speckling in the Great Tit correlates with eggshell thickness and calcium availability. We investigated whether eggshell speckling changed in a Great Tit population during a period when soil calcium declined, and estimated changes in eggshell thickness. Methods: Eggshell pigmentation of 2313 Great Tit clutches was recorded in 1988–2007 across a geological gradient in Wytham Woods, UK. Soil surveys conducted in 1974 and 1991 were repeated in 2008. Temporal and spatial changes in eggshell speckling and soil calcium were examined using generalized linear mixed models. We also estimated the change in eggshell thickness over this period. Results: Soil-calcium availability declined 1974–2008 especially in calcium-rich limestone areas. A systematic change in eggshell speckling, approximating to a 6.5% reduction in eggshell thickness, occurred between 1988 and 2007. The change was greatest in parts of Wytham that experienced the greatest decline in soil calcium. Hatching success was unaffected. Conclusion: Soil-calcium availability has declined in Wytham Woods, affecting Great Tit eggshell characteristics. This is the first evidence that declining soil calcium affects birds nesting in calcium-rich areas. Practical applications of these findings are considered.